The Effect of the Credit Crunch on Output Price Dynamics: The Corporate Inventory and Liquidity Management Channel* - Kim, Ryan (Quarterly Journal of Economics, 2020)
Abstract I study how a credit crunch affects output price dynamics. I build a unique micro-level data set that combines scanner-level prices and quantities with producer information, including the producer’s banking relationships, inventory, and cash holdings. I exploit the Lehman Brothers failure as a quasi-experiment and find that the firms facing a negative credit supply shock decrease their output prices approximately 15% more than their unaffected counterparts. I hypothesize that such firms reduce prices to liquidate inventory and generate additional cash flow from the product market. I find strong empirical support for this hypothesis: (i) the firms that face a negative bank shock temporarily decrease their prices and inventory and increase their market share and cash holdings relative to their counterparts, and (ii) this effect is stronger for the firms and sectors with a high initial inventory or small initial cash holdings.